Reaksi Kimia dalam Senyawa Psikoaktif: Penelitian Tentang Efek Kafein dan Toebromin dalam Tubuh Manusia - anggita, ardina davi (Maliki Interdisciplinary Journal, 2025)
Theobromine and caffeine are natural alkaloids found in various plants, such as tea, cocoa, and coffee, which have psychoactive effects on the human central nervous system. The effects of both theobromine and caffeine differ in mechanism and intensity. The mechanisms of toebromin and caffeine are similar and act as stimulants, but the side effects of toebromin are considered milder than caffeine. This article discusses the chemical reactions involved in making psychoactive compounds, specifically the two main components, namely caffeine and theobromine. This article focuses more on analyzing the chemical reaction stages involved in the formation of caffeine and theobromine and explores the role of enzymes and catalysts in this process. This article also discusses how caffeine and theobromine impact the body by considering pharmacokinetic and pharmacodynamic aspects. It is hoped that this article will provide a deeper understanding of the potential of these two compounds, not only in the health sector but also in the food and pharmaceutical industries, as well as the positive and negative effects of toebromin and caffeine depending on the dose and consumption pattern.